High Prevalence of Hyperhomocysteinemia in Patients with Inflammatory Bowel Disease: a Pathogenic Link with Thromboembolic Complications? - Cattaneo, Marco; Vecchi, Maurizio; Zighetti, Maddalena L.; Saibeni, Simone; Martinelli, Ida; Omodei, Paolo; Mannucci, Pier Mannuccio; Franchis, Roberto de (Thrombosis and Haemostasis, 1998)
Background and Aims. Why patients with inflammatory bowel disease are at increased risk for thrombosis is unknown. Since they may have impaired absorption of vitamins that regulate the metabolism of homocysteine, we tested the hypothesis that they have hyper-homocysteinemia, an established risk factor for arterial and venous thrombosis. Methods. The concentrations of total homocysteine (tHcy), folate and cobalamin were measured in blood samples from 61 consecutive patients with inflammatory bowel disease and 183 age- and sex-matched healthy controls. Results. The mean (± S.D.) concentration of plasma tHcy was higher in patients (12.2 ± 7.7 μmol/l) than in controls (10.5 ± 4.6, p = 0.045). Eight patients (13%) had concentrations of tHcy higher than the 95th percentile of distribution among controls, as compared with 9 healthy controls (5%, p = 0.04). The prevalence of folate deficiency was higher in patients (15%) than in controls (5%, p = 0.02). Oral administration of folate, cobalamin and pyridoxine to 15 patients for 30 days decreased their mean tHcy levels from 20.3 ± 9.9 to 9.5 ± 3.4 (p <0.001). Conclusions. In patients with inflammatory bowel disease there is an increased prevalence of hyperhomocysteinemia, which can be corrected by the administration of folate, cobalamin and pyridoxine. The high prevalence of hyperhomocysteinemia may account for the thrombotic risk of IBD patients; whether or not its correction will decrease the thrombotic risk should be tested in properly designed clinical trials.Presented at the 39th Annual Meeting of the American Society of Hematology, San Diego (CA) December 5-9, 1997, and published in abstract form in Blood 1997; 90 (supplement 1): 398a.